2008
DOI: 10.3155/1047-3289.58.12.1560
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations and Evidence for the Effectiveness of Pollution Controls on Water-Soluble Inorganic Species in Total Suspended Particulates and Fine Particulate Matter from Xi’an, China

Abstract: Total suspended particulate (TSP) and particulate matter less than 2.5 microm in aerodynamic diameter (PM2.5) samples were collected over Xi'an for a 1-yr period to characterize the seasonal variations of water-soluble inorganic ions and to evaluate the effectiveness of the pollution policies and controls during the past 10 yr. Mass concentrations of five cations (sodium [Na+], potassium [K+], ammonium [NH4+], calcium [Ca2+], and magnesium [Mg2+]) and four anions (fluoride [F-], chloride [Cl-], nitrate [NO3-],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(92 citation statements)
references
References 3 publications
8
77
1
4
Order By: Relevance
“…The water soluble Ca 2+ concentrations in PM 1 were much lower than those reported for TSP or PM 2.5 in a prior study at Xi'an (Shen et al 2008). This ion has been used as an indicator of Asian dust, which typically exhibits its highest concentrations in spring (Choi et al 2001;Cao et al 2005b;Shen et al 2007).…”
Section: Water-soluble Inorganic Ionsmentioning
confidence: 49%
See 4 more Smart Citations
“…The water soluble Ca 2+ concentrations in PM 1 were much lower than those reported for TSP or PM 2.5 in a prior study at Xi'an (Shen et al 2008). This ion has been used as an indicator of Asian dust, which typically exhibits its highest concentrations in spring (Choi et al 2001;Cao et al 2005b;Shen et al 2007).…”
Section: Water-soluble Inorganic Ionsmentioning
confidence: 49%
“…In general, sulfate, nitrate, and ammonium dominated the WS-i species studied, combining to account for 77.1%, 85.2%, 81.9%, and 83.0% of the total measured mass from spring to winter, respectively. Previous studies have suggested that gas-to-particle conversion is important, relative to the formation of these three ions, that is, SO 2 to SO 2-4 , NO 2 to NO -3 and NH 3 to NH + 4 (Lin 2002;Wang et al 2005;Shen et al 2008); and therefore, much of the PM 1 in our study apparently results from heterogeneous processes.…”
Section: Water-soluble Inorganic Ionsmentioning
confidence: 55%
See 3 more Smart Citations